MENGUJI PERAN EMOTIONAL ATTACHMENT KONSUMEN DALAM MEMBENTUK INFLUENCER INTERACTIVITY TERHADAP INFLUENCER TRUST - Wijaya, Angga Pandu; Febriatmoko, Bogy; Prananta, Widya (Bisnis-Net, 2024)
This study aims to analyze the effect of influencer interactivity on influencer trust through emotional attachment. In the current era, consumers increasingly seek credible sources of information, particularly through social media, where influencers play a crucial role in shaping consumer trust. However, limited research has focused on the role of social media interactions in fostering consumer trust toward influencers. This research employs a quantitative, causal approach to examine the relationships among the variables. Using purposive sampling with specific criteria, a total of 133 respondents participated in this study. The results indicate that influencer interactivity has a direct impact on both emotional attachment and influencer trust. The findings further demonstrate that emotional attachment partially mediates the effect of influencer interactivity on influencer trust. These results suggest that emotional attachment emerges as a mechanism influenced by influencer interactivity. Consumers are more likely to trust the information provided by influencers once emotional attachment is established. The study's implications highlight that enhancing influencer interactivity can foster consumer trust, as interaction encourages consumers to develop trust.